KEMANDIRIAN PEREMPUAN JAWA DALAM CERITA TRADISIONAL - Harjito, Harjito (LITERA, 2014)
This study aims to investigate Javanese women’s autonomy in traditional stories. The data sources were four traditional story texts. The data were collected through documentation. They were analyzed by means of the text analysis technique. The findings are as follows. First, the unavoidable life passage for adult Javanese women is marriage. In a marriage between a man and a woman, their statuses are unequal. The latter depends on the former. Second, a woman’s autonomy is apparent when she is left behind by her husband, because of either his death or his offended feeling. There are three types of Javanese women’s autonomy in traditional stories, namely protecting and taking care of children, becoming leaders, and being loyal to authorities.